(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
How do we treat a woman who gives birth to us, and whom we see as a mother, wife or as a daughter? When we open any newspaper, one of the most common things we read about females is less of their achievements and more of their dowry harassments, sexual assaults, suicides or murders. Therefore, we conducted a study to determine the pattern of deaths in females at the District Hospital, Tumkur, which is a place that is rapidly urbanising, so that preventive measures can be taken. In our autopsy study, we found that there were a total of 643 female deaths. In all, 17 deaths were due to natural causes and 626 deaths were unnatural. Suicide was the most common of unnatural deaths and dowry was the most common cause. Deaths were more common in the 21-30 years age group.